2007
DOI: 10.5194/npg-14-361-2007
|View full text |Cite
|
Sign up to set email alerts
|

Observations of linear and nonlinear processes in the foreshock wave evolution

Abstract: Abstract. Waves in the foreshock region are studied on the basis of a hypothesis that the linear process first excites the waves and further wave-wave nonlinearities distribute scatter the energy of the primary waves into a number of daughter waves. To examine this wave evolution scenario, the dispersion relations, the wave number spectra of the magnetic field energy, and the dimensionless cross helicity are determined from the observations made by the four Cluster spacecraft. The results confirm that the line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
6
24
0
Order By: Relevance
“…Using ISEE 1 and 2 observations, Hoppe et al [1981] reported that the intermediate (nonreflected and nondiffuse) ions are associated with low-frequency (∼0.03 Hz) large-amplitude upstream-propagating waves. Many studies [Eastwood et al, 2003;Narita et al, 2004Narita et al, , 2007 confirmed this finding with Cluster observations. The MHD fluctuations accompanied by reflected ions are believed to be generated by the beam instability, while the MHD fluctuations accompanied by intermediate and diffuse ions appear to be controlled by an equilibrium between the waves created by shock-accelerated ions and the ions scattered back by self-excited waves [Lee, 1982;Trattner et al, 1994;Berezhko and Taneev, 2007;Berezhko et al, 2011].…”
Section: Introductionsupporting
confidence: 60%
“…Using ISEE 1 and 2 observations, Hoppe et al [1981] reported that the intermediate (nonreflected and nondiffuse) ions are associated with low-frequency (∼0.03 Hz) large-amplitude upstream-propagating waves. Many studies [Eastwood et al, 2003;Narita et al, 2004Narita et al, , 2007 confirmed this finding with Cluster observations. The MHD fluctuations accompanied by reflected ions are believed to be generated by the beam instability, while the MHD fluctuations accompanied by intermediate and diffuse ions appear to be controlled by an equilibrium between the waves created by shock-accelerated ions and the ions scattered back by self-excited waves [Lee, 1982;Trattner et al, 1994;Berezhko and Taneev, 2007;Berezhko et al, 2011].…”
Section: Introductionsupporting
confidence: 60%
“…The characteristics of the dominant wave components are well explained by the right-hand resonant beam instability (Gary, 1993), and confirm the results of earlier Cluster data analyses (Narita et al, 2003;Narita and Glassmeier, 2005;Narita et al, 2007). The characteristics of the minor, antiparallel propagating waves can be explained by the nonresonant beam instability (Gary, 1993) or wave-wave interactions (Narita et al, 2007).…”
Section: Cluster Spacecraft In the Foreshock Regionsupporting
confidence: 84%
“…The characteristics of the minor, antiparallel propagating waves can be explained by the nonresonant beam instability (Gary, 1993) or wave-wave interactions (Narita et al, 2007).…”
Section: Cluster Spacecraft In the Foreshock Regionmentioning
confidence: 99%
“…These observations were analysed already by Narita et al (2007) using the well-established and thoroughly tested wave telescope analysis method (e.g. Neubauer and Glassmeier, 1990;Motschmann et al, 1996;Glassmeier et al, 2001;Narita et al, 2003) to study the dispersion of foreshock waves.…”
Section: Application To Cluster Fgm Observations Of Foreshock Wavesmentioning
confidence: 99%